Un ricordo di Fulvio Papi (Materiali di Estetica. Terza serie, 2024)
The article commemorates Fulvio Papi, reflecting on his legacy in Theoretical and Aesthetic Philosophy during a special volume presentation at Collegio Ghislieri, Pavia. It highlights Papi's unique ability to blend theoretical rigor with acute awareness of contemporary realities, making philosophy relevant to social issues. Papi is praised not only as a teacher to his students but also as an inspiring figure for those less immersed in philosophical studies. The article emphasizes Papi's approachable and ironically humorous demeanor, which profoundly impacted students, exemplifying his educational philosophy that extended beyond traditional academic boundaries. It underscores his role in promoting interdisciplinary teaching, leaving a lasting influence on academic and public discourse.
Keywords: Fulvio Papi; Aesthetic Philosophy; Collegio Ghislieri; Theoretical Philosophy